Equivalência de doçura entre os edulcorantes estévia e sacarose em kefir - Grayce Laiz Lima Silveira Durães (2017)
Foods made from the insertion of probiotic microorganisms are considered as functional foods. In this context, kefir can be classified as a functional food. Usually, kefir is prepared without added sugar and due to the fact that it has a marked acid taste, its acceptance to the consumer is compromised. Concurrently sucrose has been considered a villain for human health, which makes the biggest challenge for the food industry find alternative sweeteners to sucrose and safe for consumption. Therefore, the objective of this work was to determine the sweetness equivalent of stevia in relation to sucrose. Kefir was prepared with different concentrations of sucrose and stevia. Both treatments were submitted to affective and discriminatory sensorial tests to determine the equivalence of sweetness. The acceptance of kefir sweetened with sucrose by non-trained tasters was analyzed and the ideal sweetness concentration to be added to the sample was determined; The results showed that acceptance of kefir added desacarose was greater than the in natura product. With the addition of different concentrations of sucrose to kefir the sweetness concentration preferred by the tasters was determined. Then more sensitive tasters selected through the basic tastes sensitivity test determine sweetness equivalence by means of magnitude estimation. The sweetness equivalence of stevia sweetener for sucrose was 1.23% and its sweetening potency was 6.5 times sweeter than sucrose. The use of stevia in substitution of sucrose in the elaboration of kefir becomes an alternative for the food industry.